Enfoque Didáctico para la elaboración de situaciones problemáticas que abordan la construcción e interpretación de las tablas de frecuencia - Osorio Gonzales, Augusta (2018)
Dimension 1 of Wild and Pfannkuch's (1999) proposal, the PPDACcycle promotes the generation and analysis of data when a solution is given to a problematic situation that requires data collection. This research work provides evidence on the work done by a group of high school teachers when faced with a problematic situation referred to "Reading habits" that seeks to address the construction and interpretation of frequency tables. These solutions are oriented towards the development of statistical thinking; that is, it involves teachers identifying each of the stages of the PPDAC cycle. In addition, it provides evidence of the teachers' creative capacity to elaborate a new problem situation to work on frequency tables with first-year high school students. The proposed situations were evaluated through criteria to analyze creative capacity, based on the work of Torreancce (1974) and Guilford (1969).